The Role of Cholecystokinin in Peripheral Taste Signaling in Mice - Yoshida, Ryusuke; Shin, Misa; Yasumatsu, Keiko; Takai, Shingo; Inoue, Mayuko; Shigemura, Noriatsu; Takiguchi, Soichi; Nakamura, Seiji; Ninomiya, Yuzo (Frontiers in Physiology, 2017)
Cholecystokinin (CCK) is a gut hormone released from enteroendocrine cells. CCK functions as an anorexigenic factor by acting on CCK receptors expressed on the vagal afferent nerve and hypothalamus with a synergistic interaction between leptin. In the gut, tastants such as amino acids and bitter compounds stimulate CCK release from enteroendocrine cells via activation of taste transduction pathways. CCK is also expressed in taste buds, suggesting potential roles of CCK in taste signaling in the peripheral taste organ. In the present study, we focused on the function of CCK in the initial responses to taste stimulation. CCK was coexpressed with type II taste cell markers such as Gα-gustducin, phospholipase Cβ2 and transient receptor potential channel M5. Furthermore, a small subset ( 30%) of CCK-expressing taste cells expressed a sweet/umami taste receptor component, taste receptor type 1 member 3, in taste buds. Because type II taste cells are sweet, umami or bitter taste cells, the majority of CCK-expressing taste cells may be bitter taste cells. CCK-A and -B receptors were expressed in both taste cells and gustatory neurons. CCK receptor knockout mice showed reduced neural responses to bitter compounds compared with wild-type mice. Consistently, intravenous injection of CCK-Ar antagonist lorglumide selectively suppressed gustatory nerve responses to bitter compounds. Intravenous injection of CCK-8 transiently increased gustatory nerve activities in a dose-dependent manner whereas administration of CCK-8 did not affect activities of bitter-sensitive taste cells. Collectively, CCK may be a functionally important neurotransmitter or neuromodulator to activate bitter nerve fibers in peripheral taste tissues.